1990
DOI: 10.1557/proc-206-43
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Chemical Properties of Size Selected Metal Clusters: Kinetics and Saturation

Abstract: Our studies of small (n=2−40) gas phase transition metal clusters (cations, neutrals and anions) have revealed a number of size-dependent chemical and physical properties. This paper will discuss results involving activated dissociative molecular chemisorption of hydrogen (deuterium) and small alkanes on cationic, neutral and anionic platinum and gold clusters. For example, we have yet to find any size gold cluster anion to exhibit measurable reactivity towards di-deuterium, but reactivity is observed on small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
54
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 13 publications
13
54
1
Order By: Relevance
“…Calculations indicate that gold above the oxygen vacancy is electron rich as a charge transfer is imagined to take place from the support to the gold particle. Such an active site would also be consistent with gas phase experiments which demonstrated that oxygen preferred to adsorb on negatively charged clusters (170). Since there is some evidence that oxygen adsorption (and dissociation) is the rate-limiting step (87,196,388), the presence of anionic clusters is perhaps crucial to the reaction's success.…”
Section: Figure 27supporting
confidence: 78%
See 2 more Smart Citations
“…Calculations indicate that gold above the oxygen vacancy is electron rich as a charge transfer is imagined to take place from the support to the gold particle. Such an active site would also be consistent with gas phase experiments which demonstrated that oxygen preferred to adsorb on negatively charged clusters (170). Since there is some evidence that oxygen adsorption (and dissociation) is the rate-limiting step (87,196,388), the presence of anionic clusters is perhaps crucial to the reaction's success.…”
Section: Figure 27supporting
confidence: 78%
“…Cox et al examined adsorption of D2, O2 and CH4 on various sized gold clusters (170,171). The authors found that for cationic gold clusters of less than 16 atoms, deuterium readily adsorbed.…”
Section: Chemistry Of Gold Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies have shown that the reactivities of small gas-phase gold clusters (Au n in the range of up to 30 atoms) depend on the number of atoms and the charge state of the clusters, with cluster anions with an even n showing enhanced reactivity. [23,24] These observations were confirmed and extended more recently, [25,26] including observations of oddeven oscillations in the O 2 adsorption probability, which correlate with those measured for vertical detachment energies (vDEs). [27] It has been shown theoretically that the reactivity toward oxygen of gold cluster anions originates from their propensity to transfer electronic charge into the antibonding 2p* orbital of molecular oxygen, thus weakening the OÀO bond which becomes activated into a superoxo-or peroxo-like state; a similar charging effect occurs upon bonding of CO to charged (gas-phase or supported) gold clusters.…”
Section: Introductionsupporting
confidence: 77%
“…In addition, the reactive clusters adsorb just one O 2 molecule. The relative reactivities correlate well with measured electron affinities of neutral clusters, suggesting a mechanism involving the adsorption of O 2 as a one-electron acceptor [36,37]. The reactivity of gold cluster anions with CO also shows a distinct size-selectivity, although less pronounced than that with O 2 [38].…”
Section: Catalytic Processes On Free Metal Clusterssupporting
confidence: 56%